2018
DOI: 10.1016/j.procbio.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and characterization of a cold-adapted endo-1,4−β−glucanase gene from Bellamya chinensis laeta

Abstract: Highlights ・A cold-adapted endo-1,4--glucanase from Bellamya chinensis laeta (BC-EG70a) was expressed in Pichia pastoris GS115. ・The optimum pH and temperature of rBC-EG70amature and rBC-EG70aCatD were the same (pH 5.5 and 50 o C). ・At lower temperature (30 o C), the specific activity of rBC-EG70amature toward soluble cellulose was 5 to 20-fold higher than those of Trichoderma reesei and Trichoderma viride cellulases. ・rBC-EG70acatD demonstrated higher activity than rBC-EG70amature in the 10%, 15% and 20% (v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…rEf-Amy I and II maintain their enzymatic activities at the concentration of 40% ethanol. In simultaneous saccharification and fermentation (SSF) process, the ethanol concentration increased up to 15%∼20% [ 7 , 29 , 30 ]. It was found that rEf-Amy I and II could be used for this process.…”
Section: Resultsmentioning
confidence: 99%
“…rEf-Amy I and II maintain their enzymatic activities at the concentration of 40% ethanol. In simultaneous saccharification and fermentation (SSF) process, the ethanol concentration increased up to 15%∼20% [ 7 , 29 , 30 ]. It was found that rEf-Amy I and II could be used for this process.…”
Section: Resultsmentioning
confidence: 99%
“…One unit (U) of re Au glu12A activity was defined as the quantity of β‐1,3‐1,4‐glucanase that released 1 µmol/min of reduced sugars under the mentioned conditions. The protein concentration was measured using the Bradford method, with bovine serum albumin serving as the standard (Ueda et al., 2018).…”
Section: Methodsmentioning
confidence: 99%